Olive mill wastewater valorization through steam reforming using hybrid multifunctional reactors for high-purity H-2 production - Cláudio Rocha (2022)
The main purpose of this study was to assess the benefits of different hybrid multifunctional reactors (sorptionenhanced reactor (SER), membrane reactor (MR) and sorption-enhanced membrane reactor (SEMR)) comparatively to a traditional reactor (TR) for H2 production through the steam reforming of olive oil mill wastewater (OMWSR). In all reactor configurations, an in-house prepared Ni-Ru/Ce-SiO2 catalyst was used, combined in the SERs with a potassium-promoted hydrotalcite-based sorbent to capture CO2. Additionally, in the MR and SEMR configurations, a commercial Pd-Ag membrane was utilized to separate H2 from the reaction medium. It was verified an increase in both the H2 production and catalyst stability using the SER (during the prebreakthrough of CO2) in comparison with the TR. However, a higher enhancement of the H2 yield was observed using the SEMR (again during the pre-breakthrough period), which was less pronounced after the saturation of the sorbent (i.e., in the MR), due to the effect of the H2-selective membrane only. Furthermore, pure H2 can be obtained in the permeate side of the membrane reactors (in the absence of sweep gas). It was also demonstrated that the use of such multifunctional reactors (and particularly the SEMR) in the steam reforming of real olive mill effluents allows reducing drastically the pollutant load of these streams, while economically valorizing this waste with the production of green H2.